Producción y características agronómicas de estolones/m2 de pasto janeiro (Erioclhoa polystachya), a diferentes niveles de irradiación (60Co) en el cantón Babahoyo - Contreras Chariguaman, Francisco Lenin (2019)
The present research work was carried out in the premises of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at km. 7.5 of the Babahoyo-Montalvo road. The geographic coordinates in UTM were X: 1,7723946; Y: 79,7102593. The zone presents a humid tropical climate, with a temperature that oscillates between the 24 and 26 ° C, with relative humidity of 88%, annual average precipitation of 1262 mm, with height of 8 msnm and 990 hours of heliophany of annual average. As an evaluation material we used janeiro grass plants, from the material irradiated at 0; 25; 50; 75 and 100 GY of gamma rays (60 Co). In this investigation the arithmetic mean (MA), the standard deviation (SD) and the coefficient of variation (CV), used in the analysis of quantitative data, were measured. In the present investigation it was possible to determine that there are no phenotypic differences in the irradiated materials from pasture Janeiro, since all the variables evaluated did not exceed a CV> 50%, which indicates that the species may have little variability. With respect to the agronomic variables: leaf length, leaf width, number of knots per plant, leaf area, number of leaves per plant with respect to the control, the results show that the T5 treatment with a dose of 100 GY presented the highest averages. Similar results were obtained with the dry biomass variable, the T5 treatment with a dose of 100 GY and I present the highest averages with respect to the rest of the treatments